ON THE SEMIGROUP OF DIFUNCTIONAL BINARY RELATIONS - Ibrahim, Muhammad Jamilu; Sawudi , Ibrahim Mamman; Imam, Abdussamad Tanko (FUDMA JOURNAL OF SCIENCES, 2022)
In this paper, we have examine some properties of elements of the semigroup , where DX, is the set of all binary relations α ⊆ X × X satisfying , (), and is a binary operation on DX defined by () , with xα denoting set of images of x under α, and yβ−1 denoting set of pre-images of y under β. In particular, we showed that in the semigroup there is no distinction between the concepts of reflexive and symmetric relations. We also presented a characterization of idempotent elements in in term of equivalence relations.